Evaluation of a strapless heart rate monitor during simulated flight tasks. Issue 3 (3rd March 2016) - Wang, Zhen; Fu, Shan
ABSTRACT: Pilots are under high task demands during flight. Monitoring pilot's physiological status is very important in the evaluation of pilot's workload and flight safety. Recently, physiological status monitor (PSM) has been embedded into a watch that can be used without a conventional chest strap. This makes it possible to unobtrusively monitor, log and transmit pilot's physiological measurements such as heart rate (HR) during flight tasks. The purpose of this study is to validate HR recorded by a strapless heart rate watch against criterion ECG-derived HR. Ten commercial pilots (mean ± SD : age: 39.1 ± 7.8 years; total flight hours 7173.2 ± 5270.9 hr) performed three routinely trained flight tasks in a full flight simulator: wind shear go-around (WG), takeoff and climb (TC), and hydraulic failure (HF). For all tasks combined (overall) and for each task, differences between the heart rate watch measurements and the criterion data were small (mean difference [95% CI]: overall: −0.71 beats/min [−0.85, −0.57]; WG: −0.90 beats/min [−1.15, −0.65]; TC: −0.69 beats/min [−0.98, −0.40]; HF: −0.61 beats/min [−0.80, −0.42]). There were high correlations between the heart rate watch measurements and the ECG-derived HR for all tasks (r ≥ 0.97, SEE < 3). Bland-Altman plots also show high agreements between the watch measurements and the criterion HR. These results suggest that the strapless heart rate watch provides valid measurements of HR during simulated flight tasks and could be a useful tool for pilot workload evaluation.